2012
DOI: 10.1007/s00701-012-1569-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for contralateral acute epidural hematoma following acute subdural hematoma evacuation: five new cases and a short literature review

Abstract: Lower preoperative GCS score is an independent risk factor for prognosis of contralateral AEDH after ASDH. Postoperative management should include assessment of AEDH in patients treated for contralateral skull fractures and who experienced intraoperative acute brain swelling. We recommend early decompression with a burr-hole craniotomy, immediately followed by a decompressive craniectomy. This strategy provides gradual decompression, while advancing the initial surgical time and preventing the suddle decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 25 publications
1
57
1
4
Order By: Relevance
“…However, operations for traumatic intracranial hematomas are usually unilateral. Bilateral operations have been reported in bifrontal decompressive craniectomies for brain swelling15) or sequential contralateral removal of a newly developed hematoma after a one-side evacuation of an intracranial hematoma11,16,17,20). In our series of patients over 5 years, only 1.2% of the head-injury patients with hematomas underwent simultaneous operations for bilateral intracranial hematomas in a single session.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, operations for traumatic intracranial hematomas are usually unilateral. Bilateral operations have been reported in bifrontal decompressive craniectomies for brain swelling15) or sequential contralateral removal of a newly developed hematoma after a one-side evacuation of an intracranial hematoma11,16,17,20). In our series of patients over 5 years, only 1.2% of the head-injury patients with hematomas underwent simultaneous operations for bilateral intracranial hematomas in a single session.…”
Section: Discussionmentioning
confidence: 75%
“…Bilateral surgery has rarely been published in case reports for sequential evolution of a contralateral hematoma after removal of a first one7,8,10,16,17,20,21). The rate of bilateral surgery in brain trauma operations cannot be estimated, but lesions requiring consecutive contralateral surgery were almost always EDHs.…”
Section: Introductionmentioning
confidence: 99%
“…EDH is extremely rare, with only 38 cases after decompressive craniectomy presented in the literature. [25][26][27][28][29][30] Panourias et al, Matsuno et al, and Meguins et al reported contralateral epidural hematoma after decompressive craniectomy for acute subdural hematoma. 5,31,32 Shen et al evaluated published data via Pubmed and found a rate of 2.4% for contralateral EDH after acute subdural hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause appears to be corrupted equilibrium of the injured vessels and reactive ICP. 29 Meguins et al recommends intracranial pressure monitoring of TBI patients, even if decompressive surgery is performed. 26 Possible sources of bleeding include a ruptured meningeal arterial branch, venous lacerations and skull fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with such indications experience a worse condition of unconsciousness and display lateralizing signs, thus require immediate surgical intervention. 9,10,11,12,13 This case study has focused on recent findings in the anesthetic management of patients undergoing craniotomy while awake, and proposed a structured approach to the clinical practice of 'local anesthesia' for awake neurosurgery. The case holds a significant character as craniotomy for extradural hematoma is a common procedure under general anesthesia but for extradural hematoma craniotomy is not yet reported under local anesthesia.…”
Section: Introductionmentioning
confidence: 99%